Visual outcome and patient satisfaction in patients undergoing cataract surgery with premium intraocular lens implantation - Khatri, Jitesh; Gupta, Vijay; Garg, Pragya; Bairwa, Pushpendra (International Journal Of Community Medicine And Public Health, 2024)
Background: Cataract is a one of the leading cause of treatable visual impairment. Premium intraocular lens (IOL) implantation refers to the use of advanced and high-quality lenses during cataract surgery. Objective was to study the visual outcome with astigmatism correction in patients following multifocal, trifocal and EDOF IOL implantation. Methods: This hospital-based interventional study was carried on 33 patients who underwent cataract surgery with premium IOL implantation. Patients with astigmatism exceeding 1 dioptre who expressed willingness for premium IOL implantation were included in the study. Results: In the study, visual acuity and contrast sensitivity were assessed in patients who underwent Premium IOL implantation at 1 week, 6 weeks, and 3-months post-surgery. Results indicated a notable decrease in uncorrected distance visual acuity (UCDVA), uncorrected intermediate visual acuity (UCIVA), and uncorrected near visual acuity (UCNVA) compared to preoperative values across all premium IOL groups. However, contrast sensitivity exhibited a significant improvement at these specified time points after the premium IOL implantation. Conclusions: In our study, all premium IOLs effectively corrected astigmatism and met patient satisfaction needs. However, toric IOLs exhibited notably higher patient satisfaction compared to EDOF, multifocal, and trifocal IOLs.